2020
DOI: 10.3168/jds.2020-18523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xylazine administration before laparoscopic abomasopexy to correct left displaced abomasum on markers of stress in dairy cows

Abstract: Left displacement of the abomasum in dairy cows is a disease diagnosed all over the world. In Germany, a common method for its correction is laparoscopic abomasopexy (LA). The aim of the study was to assess cortisol and substance P concentrations, behavioral patterns, and feeding and rumination times during and after LA in cattle treated with xylazine before LA compared with nonsedated cattle. A total of 28 cattle that had been referred to a veterinary teaching hospital with a diagnosis of left displacement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
1
8
0
2
Order By: Relevance
“…7 Likewise, cows with LDA that had received xylazine before omentopexy had significantly greater numbers of chewing cycles per regurgitated bolus than non-treated cows (55.5 vs 46.6). 12 These findings support the recommendation of others 172 min (Group 2B) and 216 min (Group 2C) (P < 0.01) and was in the reference interval from day 2 onward. It increased further by day 30 reaching values of 305, 310 and 313 min, respectively.…”
Section: Short Communicationsupporting
confidence: 90%
“…7 Likewise, cows with LDA that had received xylazine before omentopexy had significantly greater numbers of chewing cycles per regurgitated bolus than non-treated cows (55.5 vs 46.6). 12 These findings support the recommendation of others 172 min (Group 2B) and 216 min (Group 2C) (P < 0.01) and was in the reference interval from day 2 onward. It increased further by day 30 reaching values of 305, 310 and 313 min, respectively.…”
Section: Short Communicationsupporting
confidence: 90%
“…Facial expressions were significantly different between cows not in pain compared with animals in pain [ 6 ]. Features of the pain face have been used for pain assessment in adult cattle following different procedures [ 8 , 51 , 53 ]. In calves, the use of the characteristics of the pain face or pain ears has been first described in 2017 [ 54 ].…”
Section: Pain Assessment In Calvesmentioning
confidence: 99%
“…Serum amyloid-A proteins, which are apolipoproteins associated with the high-density lipoprotein, are synthesized by the liver during the acute-phase response [52]. Although originally used as a pain biomarker [87][88][89][90], substance P can be used as a stress biomarker. Kasimanickam's group, for example, showed that its levels were higher in aggressive dairy heifers than in mild or calm heifers [91] and that its levels increased in beef heifers after undergoing Artificial Insemination at fixed time (FTAI) [92].…”
Section: Biomarkersmentioning
confidence: 99%
“…Kasimanickam's group, for example, showed that its levels were higher in aggressive dairy heifers than in mild or calm heifers [91] and that its levels increased in beef heifers after undergoing Artificial Insemination at fixed time (FTAI) [92]. Substance P can be assayed in blood using enzyme-linked immunoassays or enzyme-linked immunosorbent assays and samples can first be frozen [87,90,92]. Prolactin was originally considered a potential stress biomarker because its levels in beef heifers depend on their temperament [92] but it is not routinely used in this way because its levels are strongly influenced by dairy husbandry practices, as well as by light levels and temperature [93].…”
Section: Biomarkersmentioning
confidence: 99%